Progress of Industry 4.0 Technologies and Their Applications in Post-COVID-19 Pandemic: A Study on Image Processing AI - Arora, Makund (International Journal of Computer Sciences and Engineering, 2023)
The COVID-19 pandemic has significantly impacted various industries, leading to the adoption of advanced technologies to address the challenges faced during and after the crisis. Industry 4.0 technologies have played a crucial role in reshaping business operations and enhancing resilience. This research paper focuses on the progress of Industry 4.0 technologies, with a specific emphasis on image processing AI, and explores their applications in the post-COVID-19 era. The paper presents an overview of Industry 4.0 technologies, highlights the role of image processing AI, discusses its relevance in the context of the pandemic, and provides insights into the implementation and future potential of these technologies.